2014
DOI: 10.1517/14712598.2014.880421
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-associated antigen-A3 vaccination in the treatment of non-small-cell lung cancer

Abstract: The future is hopeful for antigen-specific immunotherapy in general and MAGE-A3 vaccine in specific. Further research needs to identify new tumor-specific antigens, more potent adjuvants and genetic profiles suggestive of a better response toward antigen-specific immunotherapy. The MAGE-A3 vaccine has to be investigated in other settings than the adjuvant one and in other tumor types expressing MAGE-A3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Nevertheless, the addition of an antigen‐specific treatment in the form of a vaccine may increase the rate of responders to immune checkpoint targeted therapy. It has been shown that vaccines against MAGE‐A3 as well as NY‐ESO‐1 can successfully induce the development of specific T‐cell responses . Because of their high tumor‐specificity and their immunogenicity, these antigens may represent a good target for specific immunotherapy of ACC.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the addition of an antigen‐specific treatment in the form of a vaccine may increase the rate of responders to immune checkpoint targeted therapy. It has been shown that vaccines against MAGE‐A3 as well as NY‐ESO‐1 can successfully induce the development of specific T‐cell responses . Because of their high tumor‐specificity and their immunogenicity, these antigens may represent a good target for specific immunotherapy of ACC.…”
Section: Discussionmentioning
confidence: 99%
“…The approved Sipuleucel-T for the treatment of metastatic prostate cancer is generated by challenging ex vivo DCs with recombinant prostatic acid phosphatase (PAP) antigen fused with GM-CSF, which enhances antigen presentation and activation of T cells against tumor cells [ 93 ]. The cancer vaccine based on direct administration of melanoma-associated antigen-A3 (MAGE-A3), a member of tumor-specific antigens expressed by various cancerous cells, is giving promising results in the treatment of resected stage IB/II non-small cell lung cancer [ 94 ]. Interestingly, emerging clinical studies on the combination of cancer vaccines (DC- or peptide-based) with ICIs (anti-CTLA4 or anti-PD-1) have shown encouraging results in melanoma patients [ 95 , 96 ].…”
Section: Cancer Immunotherapymentioning
confidence: 99%
“…The melanoma-associated antigen-A3 (MAGE-A3) is expressed on cancer cells and found in normal testis and placental cells. 46 Despite being found in normal adult tissue, its presence is not immunogenic because it does not harness human leukocyte antigen (HLA) molecules. MAGE-A3 is overexpressed in nearly 40% of stage I–II NSCLCs.…”
Section: Promoting Release Of Cancer Antigensmentioning
confidence: 99%